Subtypes of breast cancer - D. D. Pak; E. A. Rasskazova; T. V. Danilova (Опухоли женской репродуктивной системы, 2014)
Subtypes breast cancer, and also feature of a metastazirovaniye and illness recurrence are presented to survival of patients in article, and, as a result, at different subtypes. Features of diagnostics of the remote metastasises depending on a subtype breast cancer are considered. At division into subtypes breast cancer different approaches to treatment of so heterogeneous disease are necessary.